IMPLEMENTASI MODEL PJBL (PROJECT BASED LEARNING) MELALUI KEGIATAN PROGRAM EKSTRAKURIKULER ROBOTIK PADA PESERTA DIDIK SEKOLAH DASAR ISLAM TERPADU WIDYA CENDEKIA - Salsabila, Widiesti Soraya; Hendracipta, Nana; Pribadi, Reksa Adya; Andriana, Encep (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to provide an overview of the implementation of the Project-Based Learning (PjBL) model through the robotics extracurricular program at SDIT Widya Cendekia. The research employed a qualitative approach with a descriptive method. The study involved 18 participants, consisting of one vice principal, two extracurricular teachers, and fifteen students. Data collection tools included interviews and observations, and the data were analyzed using descriptive analysis techniques. The results of the study show that the robotics extracurricular program using the PjBL model was implemented by the extracurricular teachers according to the planned activities and followed the PjBL syntax. During the implementation of the Project-Based Learning model, students were observed to contribute actively, demonstrate skills, creativity, innovation, collaboration, and present their project outcomes.